A hybrid p-Si/poly(1,4-diaminoanthraquinone) photoconductive diode for optical sensor applications - Yakuphanoğlu, Fahrettin; Senkal, B. Filiz (Elsevier Science Sa, 2009)
We report on the fabrication and characterization of a hybrid Si/poly(1,4-diaminoanthraquinone) photoconductive diode for optical sensor applications. The electrical and photoconductivity properties of the diode have been investigated by dark current-voltage, steady-state and transient photoconductivity measurements. At lower voltages, the current mechanism of the diode is controlled by thermionic emission theory, whereas at higher voltages, the current mechanism is controlled by space charge limited current due to the electrical conductivity of the poly(1,4-diaminoanthraquinone). The ideality factor, barrier height and series resistance values of the diode were found to be 1.72, 0.82 eV and 1.15 M Omega. respectively. The steady-state photoconductivity mechanism of the diode indicates the presence of continuous distribution of trap levels. The transient photoconductivity results indicate that the photocurrent of the diode was varied from 1.81 x 10 (12) to 8.16 x 10(-7) A. This suggests that the photocurrent under the illumination of 35001x is 4.50 x 10(5) times higher than the dark current. It is evaluated that the hybrid Si/poly(1,4-diaminoanthraquinone) device is a photoconductive diode with photovoltaic properties. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Inorganic/organic; Photodiode; Organic semiconductor